Molecular and functional changes in neutrophilic granulocytes induced by nicotine: a systematic review and critical evaluation - Brembach, Theresa-Charlotte; Sabat, Robert; Witte, Katrin; Schwerdtle, Tanja; Wolk, Kerstin (Frontiers in Immunology, 2023)
Background: Over 1.1 billion people smoke worldwide. The alkaloid nicotine is a prominent and addictive component of tobacco. In addition to tumors and cardiovascular disorders, tobacco consumption is associated with a variety of chronic-inflammatory diseases. Although neutrophilic granulocytes (neutrophils) play a role in the pathogenesis of many of these diseases, the impact of nicotine on neutrophils has not been systematically reviewed so far. Objectives: The aim of this systematic review was to evaluate the direct influence of nicotine on human neutrophil functions, specifically on cell death/ damage, apoptosis, chemotaxis, general motility, adhesion molecule expression, eicosanoid synthesis, cytokine/ chemokine expression, formation of neutrophil extracellular traps (NETs), phagocytosis, generation of reactive oxygen species (ROS), and net antimicrobial activity, enzyme release. Material and methods: This review was conducted according to the PRISMA guidelines. A literature search was performed in the databases NCBI Pubmed® and Web of ScienceTM in February 2023. Inclusion criteria comprised English written research articles, showing in vitro studies on the direct impact of nicotine on specified human neutrophil functions. Results: Of the 532 originally identified articles, data from 34 articles were finally compiled after several evaluation steps. The considered studies highly varied in methodological aspects. While at high concentrations (>3 mmol/l) nicotine started to be cytotoxic to neutrophils, concentrations typically achieved in blood of smokers (in the nmol/l range) applied for long exposure times (24-72h) supported the survival of neutrophils. Smoking-relevant nicotine concentrations also increased the chemotaxis of neutrophils towards several chemo-attractants, elevated their production of elastase, lipocalin-2, CXCL8, leukotriene B4 and prostaglandin E2, and reduced their integrin expression. Moreover, while nicotine impaired the neutrophil phagocytotic and anti-microbial activity, a range of studies demonstrated increased NET formation. However, conflicting effects were found on ROS generation, selectin expression and release of -glucuronidase and myeloperoxidase. Conclusion: Nicotine seems to support the presence in the tissue and the inflammatory and selected tissue-damaging activity of neutrophils and reduces their antimicrobial functions, suggesting a direct contribution of nicotine to the pathogenesis of chronic-inflammatory diseases via influencing the neutrophil biology.